The effectiveness of a new parent education intervention program for primary school-age children and parents in Hong Kong - Heidi Ka Ying Lo; Tommy Kwan Hin Fong; Calvin Pak Wing Cheng; Vivian Wai Yan Lui; Yiu Pan Wong; Phyllis Kwok Ling Chan (PLoS ONE, 2025)
In Hong Kong, there is a recognised service gap and societal need for effective and evidence-based parenting education within mental health interventions. This study indtrocues the Parent Education in Mental Health (PEMH) intervention based on a theoretical framework. From 2021 to 2022, 2,246 parents from six elementary schools in Hong Kong participated in the PEMH program. An initial evaluation was conducted to asesses the effect of PEMH, with assessments at baseline and post-program. Parental stress was assessed by the Parental Stress Scale (PSS-18), parental self-efficacy was measured by the General Self-Efficacy Scale (GSE-10), the parenting style was evaluated by the Parenting Styles and Dimensions Questionnaire (PSDQ), and children’s mental health outcomes were measured using the Strengths and Difficulties Questionnaires (SDQ). Results showed that participation in the PEMH program led to significant improvements in parental stress, general self-efficacy, children’s mental health outcomes and shifts towards an authoritative parenting style. Focus groups conducted as part of the study highlighted the importance of social support in managing childcare stress and identified key components of the program for future enhancements. Parental stress was significantly associated with self-efficacy, parenting styles, and perception of children’s difficulties, while socioeconomic factors including higher educational level and income were associated with better parental and child outcomes. Our findings underscore the effect of PEMH in strengthening parental outcomes and child well-being, suggesting that a broader imputation of PEMH could be beneficial, particularly for parents of preschoolers.